Follow up and comparative assessment of IgG, IgA, and neutralizing antibody responses to SARS-CoV-2 between mRNA-vaccinated naïve and unvaccinated naturally infected individuals over 10 months - Salma, Younes (2023)
BackgroundEvidence on the effectiveness of vaccination-induced immunity compared to SARS-CoV-2 natural immunity is warranted to inform vaccination recommendations. AimIn this study, we aimed to conduct a comparative assessment of antibody responses between vaccinated naïve (VN) and unvaccinated naturally infected individuals (NI) over 10 Months. MethodThe study comprised fully-vaccinated naïve individuals (VN; n = 596) who had no history of SARS-CoV-2 infection, and received two doses of either BNT162b2 or mRNA-1273, and naturally infected individuals who had a documented history of SARS-CoV-2 infection and no vaccination record (NI cohort; n = 218). We measured the levels of neutralizing total antibodies (NtAbs), anti-S-RBD IgG, and anti-S1 IgA titers among VN and NI up to ∼10 months from administration of the first dose, and up to ∼7 months from SARS-CoV-2 infection, respectively. To explore the relationship between the antibody responses and time, Spearman's correlation coefficient was computed. Furthermore, correlations between the levels of NtAbs/anti-S-RBD IgG and NtAbs/anti-S1 IgA were examined through pairwise correlation analysis. ResultsUp to six months, VN individuals had a significantly higher NtAb and anti-S-RBD IgG antibody responses compared to NI individuals. At the 7th month, there was a significant decline in antibody responses among VN individuals, but not NI individuals, with a minimum decrease of 3.7-fold (p < 0.001). Among VN individuals, anti-S1 IgA levels began to decrease significantly (1.4-fold; p = 0.007) after two months, and both NtAb and S-RBD IgG levels began to decline significantly (NtAb: 2.0-fold; p = 0.042, S-RBD IgG: 2.4-fold; p = 0.035) after three months. After 10 months, the most significant decline among VN individuals was observed for S-RBD-IgG (30.0-fold; P < 0.001), followed by NtAb (15.7-fold; P < 0.001) and S-IgA (3.7-fold; P < 0.001) (most stable). Moreover, after 5 months, there was no significant difference in the IgA response between the two groups. ConclusionThese findings have important implications for policymakers in the development of vaccination strategies, particularly in the consideration of booster doses to sustain long-lasting protection against COVID-19.